Análise bibliométrica da produção científica sobre a jabuticabeira (Plinia sp.) - Pontes, Ana Paula Stedille (2023)
Science produces knowledge and has the need and commitment to make it public, giving feedback to the scientific community on the activities carried out during research by disclosing partial or final results, usually in scientific journals. Therefore, due to the need for studies and evaluation of scientific production and communication activities in the different areas of knowledge, bibliometrics emerged, which encompasses a series of studies that allow analyzing and obtaining indicators of the real condition of scientific production on a given subject. With the development of new technologies and the deepening of research, combined with the use of economic bases, Brazil is an important food production hub, in which fruits stand out. However, despite the country being one of the largest centers of plant diversity, native fruit trees have not yet established themselves in the context of Brazilian agribusiness, whether due to lack of exploration and research or lack of knowledge of their real productive potential. Among the native fruit trees that can be easily commercialized due to the characteristics they present in terms of flavor and functional properties of their fruits and due to their wide adaptation to the different edaphoclimatic conditions of the country, there are the jabuticaba trees. This native fruit has been demonstrating in recent years, through scientific publications, numerous potentialities and possibilities of use. As bibliometrics allows examining the production of articles, the objective of this work was to measure and analyze the state of the art regarding this native fruit tree. The data presented in this work were collected from an online database of the Web of Science (Thomson Reuters), selecting the articles that highlight the keywords used. 459 articles were found from 12 search terms. It was found that the jabuticaba tree has been attracting interest from the international scientific community, with an increase in publications related to this fruit tree in recent years. The main area of studies is related to human health, requiring dissemination of knowledge about aspects of crop management. Brazilian public universities stand out in research carried out around the world with this fruit tree, being present in the states where this fruit tree naturally occurs.